Simulation-based performance and economic evaluation of a solar thermal cooling system for a warehouse in Alkofra, Libya - Abdelwanes, Abdelsalam; King, Peter; Wijayantha, Upul K. G.; Patchigolla, Kumar; Renaldi, Renaldi (American Society of Mechanical Engineers (ASME), 2026)
Efficient cooling is crucial to avert the 30–50% postharvest losses of agricultural products in warm climates when temperature control fails, preserving food quality and the integrity of the supply chain. The need for energy to cool buildings is rising globally, especially in hot countries. Most of this increase is to meet medium- and large-scale refrigeration demands to keep agricultural produce fresh. A novel solar cooling system to meet such demand is highly desirable to help meet the increased demand for energy, reduce CO2 emissions, and cut electricity costs, especially in hot and arid areas. This research proposes a thermal solar cooling system to meet refrigeration demand. The proposed system was investigated for a hot and arid environment using trnsys 18 software. The main system variables, such as thermal solar collector area, collector slope angle, and storage capacity, were explored regarding solar fraction, coefficient of performance, and primary energy saving. The results demonstrate that a solar cooling system to cool a warehouse of 144-m2 area used to store 112 tons of fruits and vegetables at 6–8 °C requires an evacuated tube solar collector of area 1173 m2 supplied by TVP SOLAR with a claimed solar to thermal efficiency of 72%. Also, the solar panel gradient to achieve the highest values of solar fraction was 30 deg, with 60 m3 storage capacity and collector pump flowrate of 20.8 kg/s with a backup system (boiler 100 kWh capacity), to achieve the highest values of solar fraction, coefficient of performance of the whole system, coefficient of performance (COP) of absorption chiller, and primary energy saving 0.53, 0.24, 0.68, and 0.24, respectively. However, financial analysis showed that the investment cost of the proposed system is 45% higher than that of the traditional system, the vapor compressor chiller system, in terms of £/Wh. However, the solar thermal cooling system's ongoing (running) cost was 60% cheaper than a vapor compressor cooling system. Moreover, the investment payback period was nearly 10 years. Finally, CO2 emissions would be reduced by nearly 35% per annum by utilizing the proposed system compared to a vapor chiller compressor system.
Keywords: solar thermal cooling; single-effect absorption chiller; refrigeration demand; air conditioning; efficiency; energy; renewable; simulation; 40 Engineering; 7 Affordable and Clean Energy; 4008 Electrical engineering